Relationship among capital structure, managerial ability, firm age and shareholders return in Malaysia - Matemilola, Bolaji Tunde (2015)
The study aims to achieve three objectives using the system generalized method of moments as the main estimation technique. Firstly, the study investigates top managers’managerial ability as a determinant of capital structure. Secondly, the study examines the moderating effect of top managers’ managerial ability on the relationship between debt and shareholders’ returns. Third, the study investigates the moderating effect of firm-age on the relationship between debt and shareholders’ returns. The results reveal that top managers’ managerial ability is a determinant of capital structure in Malaysia and the results are robust to alternative model specification and different capital structure proxy. Top managers’ managerial ability also positively moderate the relationship between debt and shareholders’ returns in Malaysia. In addition, the firm-age positively moderates the relationship between debt and shareholders’ returns. The implications of the findings are as follow: shareholders need to conduct research to understand the management capital structure strategy. This is because good capital structure decisions that maximize interest tax-shield, and increase the return to shareholders reflects top managers’ ability. Top managers need to update their skills as well as maintain a sustainable debt level in their capital structure that increases the shareholders’ returns. Policymakers should be more specific about the top managers’ education and experience requirements, and create the enabling environment for further managerial development. The study contributes to the literature in two main ways. Firstly, unlike previous studies that uses dummy variable to measure managerial ability, this study quantify and develops an index (average) measure of top managers’ managerial ability. Secondly,unlike previous study that assumes that increase in capital structure and shareholders’returns reflect top managers’ managerial ability, this study separates managers’ ability from capital structure and return components. This approach allows top managers’managerial ability to directly affect firms’ capital structure and to moderate debtshareholders’returns relationship.